WI-FI TM, BLUETOOTH TM, ZIGBEE TM AND WIMAX TM - Labiod, H.; Afifi, H.; Santis, C. De.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
Wi-Fi$1!"(B, Bluetooth$1!"(B, ZigBee$1!" (Band WiMax$1!" (Bwill provide a complete and detailed description of the recent wireless technologies including Wi-Fi, Bluetooth, ZigBee and WiMAX. These technologies are considered to be important topics in the telecommunication industry in the next decade. Some critical subjects will be particularly developed such as security, quality of service, roaming and power conservation. Wi-Fi$1!"(B, Bluetooth$1!"(B, ZigBee$1!" (Band WiMax$1!"(Bwill also include some chapters on practicals aspects.s
Wi-FiTM: Architecture and Functions -- BluetoothTM: Architecture and Functions -- IEEE 802.15.4 and ZigBeeTM -- WiMAXTM and IEEE 802.16 -- Security in WLAN, WPAN, WSN and WMAN through Wi-FiTM, BluetoothTM, ZigBeeTM and WiMAXTM -- Practising.
Keywords: Engineering; Computer organization; Electrical engineering; Electronic circuits; Engineering; Communications Engineering, Networks; Signal, Image and Speech Processing; Circuits and Systems; Electrical Engineering; Computer Systems Organization and Communication Networks; Electronic books